Public education expenditures and growth in Greece over the period 1960-2000 - Prontzas , Panagiotis; Tsamadias, Constantinos; Papageorgiou, Petros (SPOUDAI Journal of Economics and Business, 2009)
This study seeks to estimate the impact of public education expenditures on Greek economy’s growth rates over the period 1960-2000. By applying the model introduced by Mankiw et al. (1992), up to 60% of Greece’s economic growth during a 40 year period is examined. The findings of the empirical analysis reveal that public education expenditures had a positive, statistically significant but quite low effect on economic growth in Greece. The results are not robust, when public education expenditures split on the three levels of education. JEL Classifications: O11, E62